Improving Speaking Skills through Songs: A Case Study of Moroccan EFL Classrooms - Laghrissi, Rajaa; Smirkou, Ahmed (Journal of English Language Teaching and Applied Linguistics, 2026)
ABSTRACT Listening and speaking are "solicited but neglected" skills in the EFL context of Moroccan classrooms, often sidelined by a teacher-centered approach that focuses on covering the coursebook. Linguistically, this study parallels language acquisition, where the learner moves from a passive "sea of spoken language" to production by focusing on the importance of instruction that prioritises the development of these foundational skills. Adopting a mixed-methods, quasi-experimental approach working with seventy Common Core students and thirty teachers in Casablanca, the study assesses the impact of music instruction as a "creative strategy" to bridge the gap between curricula and classroom practice. The research highlights that the strategic use of melodic input contributes to reducing the "Affective Filter" and leads to a 94.3% boost in students’ motivation, with a notable improvement in speaking fluency (91%) and vocabulary learning (88%). Through the induction of the "Song Stuck in My Head" (SSIMH) effect, music works as a cognitive bridge to repair long-standing oral deficits and break the "silent classroom" cycle. This study offers a game-changing pedagogical approach, demonstrating that when learners are able to transition from rote practice to "free and imaginative" language use, they can effectively use the target language.